BIOPESTISIDA DARI EKSTRAK DEDAUNAN UNTUK MEMBASMI HAMA TANAMAN DI JAWA BARAT - Iwan Ridwan Yusup; Dwi Kurniawan; Dwi Ratna Julianti; Lia Fakhriah; Lita Nurul Awalliyah (Percetakan Umi Toaha Makassar, 2021)
Biological pesticides or known as biopesticides are pesticides made from the main ingredients derived from living things or biological materials. Biopesticides can be used to control plant diseases or pests that can disturb, attack or damage these plants. The purpose of this study was to analyze the effectiveness of leaf extracts in eradicating plant pests. This research uses different methods depending on the type of leaves used, namely by boiling and mashing. The leaves used are papaya leaves, soursop leaves, lemongrass and betel leaves. Based on the research results, it is knowns that both betel leaf and soursop leaf are superior to be used as natural biopesticides. This is because both contain essential oils to kill plants pests.